Engineers of Jihad: The Curious Connection between Violent Extremism and Education By Diego Gambetta and Steffen Hertog (American Journal of Islam and Society, 2020)
Perhaps it’s hard to imagine an engineer who is also a poet. After all, there seems to be a stark difference between the skills required by each profession. The dichotomy is undergirded by the notion that—whether engineering conditions engineers to act in particular ways, or engineers are born with a certain mindset—engineers possess certain traits, which lead them to do some things rather than others. The present title, Engineers of Jihad, examines the connection between education and another trait: the capacity for violence. The authors are particularly interested in why there is a disproportionate number (indeed, a significant overrepresentation) of engineers among the ranks of Muslim extremists. Based on this observation, they conclude that engineers are more prone to radicalization than other university graduates (11-16). Although the data could be explained by another hypothesis (there is a higher demand for engineers in extremistgroups), the authors maintain that engineers possess certain character traits that predispose them to radicalization (164).To read the full book review, download the PDF file on the right.